POLA PERILAKU MEMBUANG SAMPAH MASYARAKAT KAMPUNG SANGIR KELURAHAN TITIWUNGEN SELATAN DI DAERAH ALIRAN SUNGAI SARIO - Yudistira, Hardani (Universitas Sam Ratulangi, 2013)
The high economic activity implies a lack of awareness about the importance of environmental cleanliness. It is generally caused due to the mindset that tends to prioritize the needs of their lives than take the time to clean up their neighborhoods.For absolute waste problem must be handled jointly between the government, non-governmental organizations and the community itself. Therefore, it needs awareness and commitment towards changing attitudes, behaviors and ethics-based culture and the environment.It was not with the villagers Sanger each household only communicate more with family incest, the level of interaction between them just look a little familiar at the time of the column and the worship of the Church. However, after the completion of it they assume that everyone is busy with their respective activities that behavior scolds mutual greetings with familiar among the They become stiff. It affects their behavior until they are about hygiene, in addition to losing the confidence to Manado City Government, they do as they wish acvities.Keywords : behavior, culture, environment